Proceedings of the 2020 Federated Conference on Computer Science and Information Systems 2020
DOI: 10.15439/2020f92
|View full text |Cite
|
Sign up to set email alerts
|

BoostSole: Design and Realization of a Smart Insole for Automatic Human Gait Classification

Abstract: This paper presents BoostSole; a smart insole based system for automatic human gait recognition. It consists of a smart instrumented insole connected to the cloud via the patient's smartphone using low-power wireless communication. First, the design of BoostSole is introduced with discussions of sensors choice, placement, calibration, and data communication. Next, an adaptive multi-boost classification algorithm is deployed to accurately identify different gait patterns. The algorithm is fast and lightweight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, STTTA had the inherent limitation of decreased state classification accuracy due to shuffling of the swing foot in the patient group. Djamaa et al [ 28 ] used the GRF to classify the walking state as shuffle walk, toe walk, and normal walk, and demonstrated that such classification could be useful in diagnosing the presence of a disorder. However, this method too could not avoid the classification error caused by shuffling.…”
Section: Discussionmentioning
confidence: 99%
“…However, STTTA had the inherent limitation of decreased state classification accuracy due to shuffling of the swing foot in the patient group. Djamaa et al [ 28 ] used the GRF to classify the walking state as shuffle walk, toe walk, and normal walk, and demonstrated that such classification could be useful in diagnosing the presence of a disorder. However, this method too could not avoid the classification error caused by shuffling.…”
Section: Discussionmentioning
confidence: 99%
“…72 h), while Digitsole [ 30 ] and Arion [ 32 ] offered only 8 and 10 h, respectively, or Mustufa’s et al solution [ 20 ], which provided only 120 min of work. There is no need for device calibration as it works properly from the moment one turns it on—in contrast to many other solutions, such as Arion and Digitsole, as shown in [ 16 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sensors 2023, 23, x FOR PEER REVIEW sensors and 1 bend sensor (black rectangle) [40] (Reprinted with permission from [12], 2023 MDPI, and [40], 2023 IEE Xplore)…”
Section: Sensor Chair (Sitting Ergonomics + Automotive Design)mentioning
confidence: 99%